The story of Owen : dragon slayer of Trondheim / E K Johnston - Johnston, E. K.
Listen! For I sing of Owen Thorskard: valiant of heart, hopeless at algebra, last in a long line of legendary dragon slayers. Though he had few years and was not built for football, he stood between the town of Trondheim and creatures that threatened its survival. There have always been dragons. As far back as history is told, men and women have fought them, loyally defending their villages. Dragon slaying was a proud tradition. But dragons and humans have one thing in common: an insatiable appetite for fossil fuels. From the moment Henry Ford hired his first dragon slayer, no small town was safe. Dragon slayers flocked to cities, leaving more remote areas unprotected. Such was Trondheim's fate until Owen Thorskard arrived. At sixteen, with dragons advancing and his grades plummeting, Owen faced impossible odds armed only with a sword, his legacy, and the classmate who agreed to be his bard. Listen! I am Siobhan McQuaid. I alone know the story of Owen, the story that changes everything.